PENGEMBANGAN ECO-WISATA UNTUK MENDUKUNG LINGKUNGAN BERKELANJUTAN DI KAWASAN PESISIR - Arisena, G.M.K.; Saputra, K.E.; Budiasa, I.K.M.; Dharmadiatmika, I.M.A.; Setiawan, I.G.B.D.; Sukendar, N.M.C.; Dewi, N.L.M.I.M.; Sudarma, I.M.; Djelantik, A.A.A.W.S.; Krisnandika, A.A.K. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p13, 2024)
The Bali island is one of the tourist destinations, both natural and cultural tourism which is well known abroad. Currently tourism in Bali is promoted through digital marketing which has a positive effect from an economic perspective. However, apart from having a positive impact, digital tourism promotion can also have a negative impact which, if not paid attention to, will cause losses to the tourist area itself. These problems show that there is a need for quality tourism, in order to save Bali from the erosion of social and cultural values ??due to tourists. Therefore, the concept of sustainable tourism is very important for the public to understand, starting from the bottom up. Through the International Partnership Program and Community Engagement activities with the theme Developing Eco-Tourism to Support Sustainable Environment in Littoral Space which brings in speakers in the fields of sustainable architecture and digital development, it is hoped that they will be able to provide concepts in making tourism more sustainable and can provide related ideas. advertising and prohibitions or restrictions on tourists through digital media. This activity is carried out using the methods of counseling, mentoring, social action/beach cleaning, and final evaluation of the activity.